The city and the war. Archaeological objects in the collection of the POLIN museum - Frączkiewicz, Marta (City and War, 2021)
In the collection of the Museum of the History of Polish Jews in Warsaw, apart from works of art, historical memorabilia and Judaica, we can also find many archaeological exhibits. Some of these objects were collected during archeological research carried out in the area where the Museum is currently located in 1998 and 2009. The others are accidental finds. The aim of the article is both to show the specificity of the objects dug out of the rubble of the Warsaw Ghetto, and to try to convey the story that these objects tell us. Since we are not able to obtain information about the “biographies of things” excavated from the ground from their original owners, invaluable information about the history of the objects, as well as people to whom they formerly belonged, constitutes their state of preservation and the place where they were found. The archaeological exhibits discussed in the text testify to the life and everyday life of the ghetto inhabitants, while reminding us of their tragic fate.